REZZAG BARA Ahmed.Defect effect on the electric characteristics of Schottky contacts - GUEDIRI Mohamed Elfatah; REZZAG BARA Ahmed (Université of Eloued, 2025)
This thesis investigates the impact of defects on the electrical characteristics of Schottky contacts. It begins with an overview of semiconductor physics and the formation of metal– semiconductor junctions. Various methods are analyzed to extract key diode parameters such as the Schottky barrier height and ideality factor. Simulations using Atlas-Silvaco are conducted to model the influence of defects and temperature on diode behavior. The results show that defects lead to notable deviations from ideal characteristics, including increased ideality factor and barrier inhomogeneity. A comparative study of MS and MIS structures highlights the critical role of interface quality. This work contributes to a better understanding of defect-related effects and supports the design of more efficient Schottky-based devices for modern electronic systems. تبحث هذه المذكرة في تأثير العيوب على الخصائص الكهربائية لوصلات شوتكي . تبدأ بعرض لمبادئ دن فيزياء أشباه الموصلات وتكوين وصلة مع - ات شبه موصل. تم تحليل عدة طرق لاستخلاص المعلم الأساسية للديود مثل ارتفاع حاجز شوتكي وعامل المثالية. تم إجراء محاكاة باستخدام برنامج Atlas- Silvaco أظ لنمذجة تأثير العيوب ودرجة الحرارة على سلوك الديود. هرت النتائج أن العيوب تؤدي إلى انحرافات ملحوظة عن السلوك المثالي، مثل زيادة عامل المثالية وعدم تجانس الحاجز. كما أظهرت الدراسة المقارنة بين هياكل ت MIS و MS الدور الحاسم لجودة الواجهة. تسهم هذه الدراسة في فهم أفضل لتأثيرا ر العيوب وتدعم تصميم أجهزة شوتكي أكث ية الحديثة. كفاءة للتطبيقات الإلكترون لمات الك ة: المفتاحي شوتكي. أشباه الموصلات، ارتفاع الحاجز
Master's theses: specializing in Telecommunication Systems.2025
Keywords: Semiconductor; the barrier height; Schottky; شوتكي. أشباه الموصلات، ارتفاع الحاجز،